HAKIKAT WUJUD: SEBUAH KLASIFIKASI - Husnul Khatimah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2018)
When traced by human thoughts, everyone agree that everything that exists do not exist by itself, except for a small part which according to reason, may exist without going through intermediaries. Therefore, any original object that can be transformed into various forms, become these origins have special traits and characteristics, and can be changed to another form. For example water. Water rises into the air into clouds then drops to rain, and winter to snow that is at a time becomes gas. Al-shahrastani said that in the opinion of "Anaxagoras" the origins of the body are the subtle dhat. Are the human senses and the intellect can not reach, from the dhat arises the upper and lower realms composed of the very simple dhat that make up the various forms. Unlike the exposure of Al-Ghazali that form is classified into four gradual categories: the true or dhati, the form in the mental subject, the form in the oral, and the form in writing. While the actual being is already there in concrete, real, which in the end is called necessitas, mandatory al-wujud and also potential form is something that still exist in the concept of ideas and ready to be concrete that known space and time.